2021
DOI: 10.3390/cells10092262
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology and Inflammatory Cell Characterization in 10 Autoptic COVID-19 Brains

Abstract: COVID-19 presents with a wide range of clinical neurological manifestations. It has been recognized that SARS-CoV-2 infection affects both the central and peripheral nervous system, leading to smell and taste disturbances; acute ischemic and hemorrhagic cerebrovascular disease; encephalopathies and seizures; and causes most surviving patients to have long lasting neurological symptoms. Despite this, typical neuropathological features associated with the infection have still not been identified. Studies of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…Our study revealed that the SOD2 might be another very important link between a malfunctioning immune system and oxidative stress, alongside 4-HNE. Namely, the immunohistochemical resemblance of the findings for 4-HNE and SOD2 in all the vital organs of our patients indicated a possible pathogenic interference between this crucial antioxidant enzyme specific for mitochondria (SOD2) and 4-HNE regulating mitochondrial RSO production, stability, and leakage [52]. Consequently, this could result in Fenton's reaction, ferroptosis, and the spread of lipid peroxidation, shown by the abundant immunostaining for both biomarkers.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our study revealed that the SOD2 might be another very important link between a malfunctioning immune system and oxidative stress, alongside 4-HNE. Namely, the immunohistochemical resemblance of the findings for 4-HNE and SOD2 in all the vital organs of our patients indicated a possible pathogenic interference between this crucial antioxidant enzyme specific for mitochondria (SOD2) and 4-HNE regulating mitochondrial RSO production, stability, and leakage [52]. Consequently, this could result in Fenton's reaction, ferroptosis, and the spread of lipid peroxidation, shown by the abundant immunostaining for both biomarkers.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, the lipid peroxidation trigger and 4-HNE mediated systemic vascular and oxidative stress could be associated with an uncontrolled (auto)immune stress response, which may lead to ARDS and MOF, as observed in our patients. The high importance of the malfunctioning immune system destroying vital organs, not only the lungs but even the brain, for severe/lethal SARC-CoV-2 infection is well known, even if the virus itself may not always be the [52][53][54], as is also the importance of uncontrolled oxidative stress [55,56]. Both of the supporting findings of our study suggest that lipid peroxidation, notably, 4-HNE, might be the link between these two vicious circles of lethal COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…58–60 Additionally, there is evidence of multifocal inflammatory infiltrates consisting of lymphocytes as well as activated innate immune cells in autopsy tissue. 61 Further investigation of PASC will require in-depth exploration of what is occurring in the CNS compartment during both acute and recovery time periods.…”
Section: Discussionmentioning
confidence: 99%
“…There are major vascular changes in the cerebral cortex, while there is also substantial meningeal and perivascular inflammation of the cortical parenchyma with hypoxic cellular injury. The cerebellum and brainstem often show perivascular lymphocytic inflammation of CD8-positive T cells mixed with CD68-positive macrophages [11]. The inflammatory changes typically target disrupted vascular walls suggesting prominent role of microvascular injury in COVID-19-induced neurological comorbidity [11].…”
mentioning
confidence: 99%
“…The cerebellum and brainstem often show perivascular lymphocytic inflammation of CD8-positive T cells mixed with CD68-positive macrophages [11]. The inflammatory changes typically target disrupted vascular walls suggesting prominent role of microvascular injury in COVID-19-induced neurological comorbidity [11]. The hypoxic changes are noticeable in COVID-19 patients with brainstem and cerebellar involvement [12].…”
mentioning
confidence: 99%